CFHT MegaPrime/MegaCam u-band source catalogue of the AKARI North Ecliptic Pole Wide field. Issue 1 (20th August 2020) - Huang, Ting-Chi; Matsuhara, Hideo; Goto, Tomotsugu; Shim, Hyunjin; Kim, Seong Jin; Malkan, Matthew A; Hashimoto, Tetsuya; Hwang, Ho Seong; Oi, Nagisa; Toba, Yoshiki; Lee, Dongseob; Santos, Daryl Joe D; et al.
ABSTRACT: The AKARI infrared (IR) space telescope conducted two surveys (Deep and Wide) in the North Ecliptic Pole (NEP) field to find more than 100 000 IR sources using its infrared camera (IRC). IRC's nine filters, which cover wavebands from 2 to 24 μ m continuously, make AKARI unique in comparison with other IR observatories such as Spitzer or WISE . However, studies of the AKARI NEP-Wide field sources had been limited due to the lack of follow-up observations in the ultraviolet (UV) and optical. In this work, we present the Canada–France–Hawaii Telescope MegaPrime/MegaCam u -band source catalogue of the AKARI NEP-Wide field. The observations were taken in seven nights in 2015 and 2016, resulting in 82 observed frames covering 3.6 deg^2 . The data reduction, image processing, and source extraction were performed in a standard procedure using the elixir pipeline and the astromatic software, and eventually 351 635 sources have been extracted. The data quality is discussed in two regions (shallow and deep) separately, due to the difference in the total integration time (4520 and 13 910 s). The 5σ limiting magnitude, seeing full width at half-maximum, and the magnitude at 50 per cent completeness are 25.38 mag (25.79 mag in the deep region), 0.82 arcsec (0.94 arcsec), and 25.06 mag (25.45 mag), respectively. The u -band data provide us with critical improvements to photometric redshifts and UV estimates of the precious infrared sources from the AKARI space telescope.